Pengaruh Modal Intelektual, Efisiensi Operasional, dan Pengeluaran R&D terhadap Financial Distress dengan Usia Perusahaan sebagai Variabel Moderasi - Alvin Jeryanto; Rida Prihatni; Dwi Handarini (LPPM Universitas Negeri Jakarta, 2025)
This study aims to examine the effect of intellectual capital, operational efficiency, and research and development (R&D) expenditure on financial distress, with firm age as a moderating variable. The study focuses on primary consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. A purposive sampling method was applied, and panel data regression analysis was conducted using EViews 13. The results show that intellectual capital has no significant effect on financial distress. Meanwhile, both operational efficiency and R&D expenditure have a negative and significant effect on financial distress. Furthermore, firm age does not significantly moderate the relationships between intellectual capital, operational efficiency, or R&D expenditure and financial distress. These findings emphasize the importance of efficient operations and sustained innovation efforts in mitigating financial distress, while indicating that firm age does not play a moderating role in these relationships.